Pengembangan Tari Kreasi Tari Caping Sekolah Dasar Kecamatan Bangkalan - Andika Surya Nanda (Yayasan Arrahman Nahdlatul Wathan, 2024)
Indonesia is known to be rich in culture, considering the diversity of tribes in this archipelagic country. Starting from dances that discuss the story of the struggle of the royal army, romance, to activities that people engage in every day such as farming. Hearing the name, perhaps many people can already guess that this dance tells about farming activities. The word